National Music Heritage in the Eyes of the Thinkers - Otajonov Farxod Ibroximoch (International Journal on Orange Technologies, 2021)
in this article, the works of scholars of the past, who left History in written sources, the history of which covered the historical processes associated with the peoples of Central Asia, a number of ancient scholars, such as Herodotus, Ksenofont, Diodor, gave us information about the books, historical sources. Historical written sources of our national music heritage have been thoroughly highlighted.